Magnetic silica hybrids modified with guanidine containing co-polymers for drug delivery applications; Materials Science and Engineering: C; Vol. 64 - Timin A. S. Aleksandr Sergeevich; Kashirova S. Yu. Svetlana; Rumyantsev E. V. Evgeniy; Goncharenko A. A. Alexander (2016, 2016)
Title screen